The Role of Management Information Systems in Human Resources Management in the Bengkalis Regency Education Office - Alya Yunita; Siti Murasih; Muhammad Haiqal; Titin Sumarni (Penerbit Hellow Pustaka, 2024)
This research aims to examine the role of Management Information Systems (SIM) in Human Resources (HR) management at the Bengkalis Regency Education Office, particularly in improving operational efficiency and effectiveness, data accuracy, and supporting decision making. The research method used was qualitative, with data collection through in-depth interviews with service employees and literature review. The research results show that the implementation of SIM has had a significant positive impact, including ease of HR administration, increased accuracy and reliability of data, as well as increased transparency and accountability. However, challenges such as resistance to change, training needs, and technical support remain. However, the benefits obtained from SIM are far greater than the challenges faced. This research recommends increasing training and technical support as well as regular system maintenance to ensure optimal use of SIM. In this way, SIM can continue to support improving the quality of education services in Bengkalis Regency.